Budget impact analysis of secukinumab versus adalimumab in the treatment of ankylosing spondylitis. (1st February 2019) - Purmonen, Timo; Törmälehto, Soili; Wahlman, Hanna; Puolakka, Kari
Abstract: Background: Biologic treatments have enhanced the treatment outcomes of patients with active ankylosing spondylitis (AS). Until recently, TNF-alpha-inhibitors have been the only biologics approved for the treatment of active AS. The objective of this study was to assess the potential financial impact of the first non-TNF-alpha biologic secukinumab (fully human IL-17A-inhibitor) vs adalimumab (TNF-alpha-inhibitor) in the treatment of AS in Finland. Materials and methods: In this model-based budget impact analysis, patients were treated either with secukinumab (150 mg) or adalimumab (40 mg). The number of patients and market share of different biologics were based on national reimbursement registry data. Adalimumab was the most commonly used biologic treatment for AS, and in the base case analysis all adalimumab patients are assumed to switch to secukinumab. Response rates were based on a matching-adjusted indirect comparison between secukinumab and adalimumab. Patients not achieving response were switched to another biologic treatment. Results: Treating AS patients with secukinumab instead of adalimumab leads to potential savings of 18.2 million euros within a 5-year time period. The total costs within the follow-up time were 59.5 million euros and 77.7 million euros with and without secukinumab, respectively. According to sensitivity analyses, a higher adoption rate of secukinumab corresponds to higher potential savings. Conclusions: Secukinumab is a cost-saving treatment option compared with adalimumab in the treatment of AS in Finland. More patients could be treated with a biologic by allocating resources more efficiently.